Splay–density coupling in semiflexible main-chain nematic polymers with hairpins. Issue 28 (4th July 2018) - Popadić, Aleksandar; Svenšek, Daniel; Podgornik, Rudolf; Daoulas, Kostas Ch.; Praprotnik, Matej
Abstract : A rigorous macroscopic continuity constraint with chain ends and hairpins as sources is devised and corroborated by simulations. Abstract : A main-chain nematic polymer melt/solution exhibits macroscopic orientational order of main polymer chains, i.e., a preferred (nematic) direction. It has long been known that in such polymeric liquid crystals spatial density/concentration variations and distortions of the nematic direction are coupled, obeying a vectorial continuity constraint whose rigidity increases with chain length. Its vectorial nature precludes the application to flexible chains, where backfolds (hairpins) are present and apolar nematic symmetry is manifest, which has been its puzzling feature from the beginning. We now establish a description of the splay–density coupling in the case of arbitrary backfolding, devising a continuity constraint for the "recovered" polar order of the chain tangents and introducing hairpins as its new type of sources. Performing detailed Monte Carlo simulations of nematic monodomain melts of "soft" worm-like chains with variable length and flexibility, we show via their structure factors that the weakening of the coupling due to the backfolding can be consistently quantified on the macroscopic level.